2003
DOI: 10.1098/rsbl.2003.0040
|View full text |Cite
|
Sign up to set email alerts
|

Growth trades off with habitat specialization

Abstract: How differences in niche breadth evolve and are maintained remains largely unknown. The 'jack of all trades is master of none' model of resource specialization has been widely considered, but, to our knowledge, never before supported empirically. It invokes performance trade-offs associated with specialization. Specialists should outperform generalists on a subset of resources, but be unable to maintain high performance over a broader range of resources. By contrast, generalists should perform less well, on av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 13 publications
0
73
0
Order By: Relevance
“…2 is a habitat specialist, implying that its host coral Acropora hyacinthus (in which this goby has the lowest fitness-related costs) is a rather suboptimal habitat for most Gobiodon spp. Caley & Munday (2003) observed that growth trades off with habitat specialisation among Gobiodon spp., and specialists avoid corals with high fitness-related costs. A. hyacinthus seems unsuitable for most other gobiid fishes and does not support large species, as is reflected in the very small size of Gobiodon sp.…”
Section: Discussionmentioning
confidence: 99%
“…2 is a habitat specialist, implying that its host coral Acropora hyacinthus (in which this goby has the lowest fitness-related costs) is a rather suboptimal habitat for most Gobiodon spp. Caley & Munday (2003) observed that growth trades off with habitat specialisation among Gobiodon spp., and specialists avoid corals with high fitness-related costs. A. hyacinthus seems unsuitable for most other gobiid fishes and does not support large species, as is reflected in the very small size of Gobiodon sp.…”
Section: Discussionmentioning
confidence: 99%
“…Habitat specialists can suffer as a result of their specialisation when those habitats become reduced in availability or disappear altogether (Caley & Munday 2003). The implications of habitat specialisation on populations of coral reef fishes have been difficult to determine (Sale 1991).…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…However, incompatibility selection appears to be more realistic in this case: exploitation of substantially different resources or habitats probably depends on different traits, and the impaired ability to exploit one of them does not per se help to exploit the other. Ecological tradeoffs, which force resource specialization and are necessary for speciation, are well documented in a variety of situations (12)(13)(14)(15)(16)(17)(18)(19)(27)(28)(29). Here, we assumed that the environment is homogeneous, as of free-swimming fish in a lake.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, to cause sympatric speciation, natural selection must (i) protect genetic variability within the population and (ii) tear the population apart by eliminating intermediate phenotypes, such as those of hybrids between the incipient species (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). These conditions can be met either by frequency-dependent disruptive selection acting on one trait or frequency-dependent incompatibility selection, acting on two traits and involving a fitness tradeoff between them (12)(13)(14)(15)(16)(17)(18)(19). Here we investigate the previously neglected possibility of sympatric speciation driven by incompatibility selection and argue that modes of selection behind allopatric and sympatric speciation can be essentially the same.…”
mentioning
confidence: 99%